Acupuncture at KI3 in healthy volunteers induces specific cortical functional activity: an fMRI study. Issue 1 (December 2015) - Zhu, Bo; Wang, Yanjie; Zhang, Guifeng; Ouyang, Huailiang; Zhang, Jiping; Zheng, Yu; Zhang, Shaoqun; Wu, Chunxiao; Qu, Shanshan; Chen, Junqi; Huang, Yong; Tang, Chunzhi
Abstract Background Using functional magnetic resonance imaging (fMRI), we determined brain regions that were activated/deactivated more by acupuncture at Taixi (KI3) than by non-acupoint or sham acupuncture. Methods A total of 30 healthy volunteers were randomly divided into a KI3 group (15 subjects) and non-acupoint group (15 subjects). Subjects in KI3 group received a sham acupuncture and then a real acupuncture, fMRI was performed before and after sham acupuncture as well as after ture acupuncture. Subjects in non-acupoint group received a ture acupuncture and the fMRI was performed before and after ture acupuncture. The fMRI data obtained were successively analyzed using DPARSF2.3 and REST1.8 software, yielding regional homogeneity (ReHo) and amplitude of low frequency fluctuations (ALFF) values. Results Compared with sham acupuncture, ALFF values were higher in Brodmann area (BA) 10 and lower in BA7 and BA18. ReHo values after real acupuncture at KI3 were higher in the right sub-lobar region and BA10 and were lower in BA31. Compared with the changes before and after real acupuncture at non-acupoint, the changes at KI3 showed higher ALFF valued in the left cerebellum posterior lobe, BA10, BA39, BA31 and decreased ALFF was observed in the BA18, BA19 and BA40; and higher ReHo values were shown in left cerebellum posterior lobe pyramis, left cerebellum anterior lobe. BA37, BA10, BA39, BA31 and lower ReHo values were shown in BA18 and BA31. Conclusion Acupuncture at KI3 has a specific effect on certain brain regions associated with perception, body movement, spirit, and association. Additionally, visual and auditory cortices were affected, which may be related to the clinical applications of KI3 acupuncture in auditory and cognitive disorders, hypomnesis, loss of concentration, and the loss of ability to work and learn. Trial registration The research ethics committee was achieved at 01/08/2012, the NO. was ChiECRCT-2012011. Website for Clinical Trial Registration:http://www.chictr.org.cn/showproj.aspx?proj=7123 . This study was registered at www.chictr.org, the Clinical Trial Registration Number was ChiCTR-TRC-12002427, and the registration number was achieved at 18/08/2012. The name of IRB that provided approval for the study and clearly state isChinese Clinical Trail Registry .